2005
DOI: 10.1093/geronb/60.1.s48
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Communication Problems on Caregiver Burden

Abstract: The study findings not only lend further support to the existing literature that has documented problem behaviors as strong predictors of burden but also emphasize the importance of communication problems in the caregiving process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
3
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 24 publications
7
137
3
9
Order By: Relevance
“…Previous work demonstrated that caregivers of diabetic patients may experience heightened stress [25] and caregiver burden [20,21], further increased with the amount of caregiver time with the patient [20,22]. Nevertheless, the present results showed no significant difference between caregivers and the general population in SF-36 Physical and Mental Component Summary scores (Table 4) [33,38,39].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Previous work demonstrated that caregivers of diabetic patients may experience heightened stress [25] and caregiver burden [20,21], further increased with the amount of caregiver time with the patient [20,22]. Nevertheless, the present results showed no significant difference between caregivers and the general population in SF-36 Physical and Mental Component Summary scores (Table 4) [33,38,39].…”
Section: Discussioncontrasting
confidence: 64%
“…Caregivers of patients with diabetic foot problems had overall health-related quality of life (SF-36 Physical and Mental Component Summary scores) similar to that of the general population (general population scores, 50 [38,39]) (Table 4). However, caregivers scored, on average, higher than the general population in seven of the eight SF-36 subscales (Table 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Effective communication can be used as a mediator to minimize problem behaviours. Savundranayagam et al [26] demonstrated significant correlations among communication problems and three types of caregiver burden (i.e., objective, demand and stress) suggesting that ineffective communication was related to problem behaviours and increased burden.…”
Section: Problem Behaviours and Communicationmentioning
confidence: 99%
“…[37] The three dimensions of burden are linked via communication and problem behaviours. Savundranayagam et al [26] showed that difficulties with communication deficits simultaneously impact problem behaviours on the different dimensions of burden. There were links among dementia, declining communication skills and three different types of caregiver burden (demand, stress and objective burden).…”
Section: Caregiver Burdenmentioning
confidence: 99%